Biopsy of Different Oral Soft Tissues Lesions by KTP and Diode Laser: Histological Evaluation. (27th October 2014) - Romeo, Umberto; Russo, Claudia; Palaia, Gaspare; Lo Giudice, Rossella; Del Vecchio, Alessandro; Visca, Paolo; Migliau, Guido; De Biase, Alberto
Abstract : Introduction . Oral biopsy aims to obtain clear and safe diagnosis; it can be performed by scalpel or laser. The controversy in this latter application is the thermal alteration due to tissue heating. The aim of this study is the histological evaluation of margins of " in vivo " biopsies collected by diode and KTP lasers. Material and Methods . 17 oral benign lesions biopsies were made by diode 808 nm (SOL, DenMatItalia, Italy) and KTP 532 nm (SmartLite, DEKA, Italy). Samples were observed at OM LEICA DM 2000; margin alterations were evaluated through Leica Application Suite 3.4. Results . Epithelial and connective damages were assessed for each pathology with an average of 0.245 mm and a standard deviation of ±0.162 mm in mucoceles, 0.382 mm ± 0.149 mm in fibromas, 0.336 mm ± 0.106 mm in hyperkeratosis, 0.473 mm ± 0.105 mm in squamous hyperplasia, 0.182 mm in giant cell granuloma, and 0.149 mm in melanotic macula. Discussion . The histologic aspect of lesions influenced the response to laser, whereas the greater inflammation and cellularity were linked with the higher thermal signs. Many artifacts were also associated to histologic procedures. Conclusion . Both tested lasers permitted sure histologic diagnosis. However, it is suggested to enlarge biopsies of about 0.5 mm, to avoid thermal alterations, especially in inflammatory lesions like oral lichen planus.